The Influence Of Budget Participation, Budget Goal Clarity, And Accounting Control On The Performance Of Regional Government Organizations - Cahyani, Utami Fajar; Gowon, Muhammad; Erwati , Misni (Jurnal Cakrawala Akuntansi, 2023)
The aim of this study was provided empirical evidence of the influence of participation in budgeting, clarity of budget targets, and accounting control on the performance of regional apparatus organizations in Bungo District Offices. This research included in quantitative research. The data used in this study are primary data obtained from respondents through questionnaires. The respondents of this study are the chairmans, secretaries, heads of financial subsections, and financial staff. The sample determined by the purposive sampling method. The data analysis method used is multiple linear regression analysis using SPSS 22.0. Hypothesis testing using the F test and t test. The results of this study indicate that: 1) Participation in Budget Arrangement, Budget Targets Clarity, and Accounting Control affect the Performance of Regional Apparatus Organizations, 2) Participation in Budget Arrangement affects the Performance of Regional Apparatus Organizations, 3) Clarity of Budget Objectives influences the Performance of Regional Apparatus Organizations, 4) Accounting Control influences the Organization Performance of Regional Apparatuses.